2017
DOI: 10.1038/srep43212
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects on liver, kidney and pancreas of enzymatic- and acidic-hydrolysis of polysaccharides by spent mushroom compost (Hypsizigus marmoreus)

Abstract: The present work investigated the protective effects on liver, kidneys and pancreas of spent mushroom compost polysaccharide (SCP) and its hydrolysates (enzymatic- (ESCP) and acid-hydrolyzed SCP (ASCP)) from Hypsizigus marmoreus, in streptozotocin (STZ)-induced diabetic mice. The results showed that enzymatic (superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)) and non-enzymatic activities (total antioxidant capacity (T-AOC)) were significantly increased, the lipid peroxide contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
1
11
0
2
Order By: Relevance
“…These results indicated that the protection of Grifola frondosa polysaccharides against age‐related brain impairment may be related to attenuation of oxidizing free radical–generated oxidative stress. Our results are similar to the previous works, which suggested that many favorable effects contributing in human health of mushrooms are based on their antioxidant properties .…”
Section: Discussionsupporting
confidence: 92%
“…These results indicated that the protection of Grifola frondosa polysaccharides against age‐related brain impairment may be related to attenuation of oxidizing free radical–generated oxidative stress. Our results are similar to the previous works, which suggested that many favorable effects contributing in human health of mushrooms are based on their antioxidant properties .…”
Section: Discussionsupporting
confidence: 92%
“…Arum rupicola ekstresi verilen gruplarda lipit peroksidasyona karşı sağlanan korunma, dokularda bu bitki bileşenlerinin serbest radikallere karşı antioksidan aktiviteye destek sağladığı doğrultusunda yorumlanabilir. Bu sonuçlar, bitki ekstrelerinin diyabetik komplikasyonlarda iyileştirici etkisinin araştırıldığı serbest radikal temizleyici antioksidan moleküllerinde eşzamanlı artışı ile birlikte MDA seviyesinin de azaldığını bildiren birçok çalışma ile paralellik göstermektedir [41,42,43].…”
Section: Bulgular Ve Tartışmaunclassified
“…It was observed that a vegetable like cactus ( Opuntia ficus‐indica ) could reestablish hematological parameters, decrease lipid peroxidation, and restore enzyme activities in rat liver injured by methotrexate, a chemotherapy medication used to treat cancer (Akacha, Rebai, Amri, & Zourgui, ). In counteracting the liver injury caused by streptozotocin, antioxidant activity was demonstrated in Hibiscus sabdariffa L. extract, as well as spent mushroom compost polysaccharide and its hydrolysates, leading to the improved parameters and liver function as well as lowered blood lipids (Adeyemi, Ukwenya, Obuotor, & Adewole, ; Liu et al., ). In another rat model, whole grain of Kamut khorasan wheat ameliorated doxorteubicin‐induced oxidative damage in the liver (Akacha et al., ).…”
Section: Protective Effects Of Natural Products On Drug‐induced Livermentioning
confidence: 99%